Marketing Management of Microfinance at Bank Aceh Syariah - Andriani, Winda; Asra, Asra; Muhayatsyah, Ali; Safrina, Lia (Journal of Management and Business Innovations, 2024)
This study aims to analyse the marketing management of Microfinance at Bank Aceh Syariah. The research method used is qualitative with interview techniques. The results found that the marketing strategy of Bank Aceh Syariah Samudera Branch on iB microfinance is carried out by providing several alternative channels that customers can choose from to obtain financing, employees who provide good service and are responsive. In addition, the bank provides attractive margins to customers every time there is a promo, displays the superiority of the quality and quality of these products, the varied prices offered to customers, the location or place of the bank which is well arranged for the convenience of customers and a strategic location. Advertising is done through brochures, digital media and other social media, then direct sales-based sales. There are several obstacles in implementing Bank Aceh Syariah's marketing strategy in iB microfinance, namely the cancellation of financing applications by other parties, problematic collateral such as disputed land and building certificates, impatient customers, and lack of vehicles to reach customers who are far away.Keyword: Marketing, Management, Microfinance and Bank Aceh Sharia